Use of sodium hypochlorite to reduce the concentration of Mn2+ in acid mine waters to improve the water quality of the Yauli River, Junín, Perú - Castillo Ungaro, Castillo Ungaro (2022)
In the world, most of the underground and surface water supply sources are affected by the presence of manganese Mn2+, which is one of the biggest pollutants and causes an impact on the environment. Underground mining operations generate acidic water, whose pH is between 2 and 6; however, the mining companies do not present methodologies for control. Acid water samples were obtained from the industrial area of the Carahuacra mining production unit (Volcán S.A.A. Mining Company), according to the Water Monitoring Protocol of the National Water Authority (ANA) at 4600 meters above sea level, in the province of Yauli, Junín Region. The acidic water studied has a pH between 3.5 and 5.5 and a Mn2+ concentration of up to 250 mg/L. According to current regulations, the concentration is required to be reduced below 0.2 mg/L (ECA-2017). The objective of this work is proposing the use of sodium hypochlorite (NaClO) as an oxidizing agent to allow its precipitation and separation. Tests were performed at different pH, concentrations (%) and sodium hypochlorite consumption (mg/L); achieving 99.96% Mn2+ removal. The optimum pH range achieved was between 8.5 and 8.8 while the concentration and consumption of sodium hypochlorite was 0.05% or 1.0 mg/L respectively. The present procedure can be applied by other companies to decrease the Mn2+ concentration ion.